Implementasi Penguatan Karakter Disiplin Dan Kerja Keras Melalui Kegiatan Ekstrakurikuler Karate Di Sd Djamaatul Ichwan Surakarta - Dewi, Niken Kumala; , Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
This research is motivated by the importance ofstrengthening the character of discipline and hard work. The purpose of this study to describe: 1) Implementation of the character strengthening discipline and hard work through tracurricular activities in elementary school karate DJI, 2) obstacles in strengthening implementation of the code 3) attempts to overcome these obstacles. This study is a qualitative research design phenomenology. The subject of this research is the principal, coach karate, homeroom teacher, karate teacher coordinator and some students who take extra karate. Methods of data collection using interviews, observation and documentation. Test the validity of the data using a triangulation of sources and techniques. Analysis of data using interactive models (Miles and Huberman). The results of this study showed the following: 1) the analysis of the implementation of the character strengthening discipline and hard work through extracurricular karate can be done on a regular exercise and activity TC (Training Center). Both of these activities can reinforce discipline through training schedule has been set, showed up on time, arrive on time, dressed in karate, do not break the rules that have been made, the arrival of exercise always consistent, and do positive things like implementing the Asr prayer before a workout. Hard work was also obtained from repeat mimics the movement of coaches, keep the spirit despite being tired, not quick to complain to request immediate break, ask for help coach while there is still poorly understood movements, excited as sparingan organized by the school. 2) the obstacles faced in the process of strengthening these characters are parents who lack support their participation, the characteristics of students who are still up and down enthusiasm in participating in karate, and the weather was hot and the rain which disrupted the exercise. 3) the efforts made to minimize the barriers that exist which parents are given the motivation to keep supporting his son or daughter in order to be able to perform, keep the spirit of the students that are not easily fade and provide support wherever the place of exercise should keep the spirit. Keywords: Discipline, Work Hard, Karate